FROM CAMAC TO WIRELESS SENSOR NETWORKS AND TIME-TRIGGERED SYSTEMS AND BEYOND: EVOLUTION OF COMPUTER INTERFACES FOR DATA ACQUISITION AND CONTROL. PART I - Zalewski, Janusz (International Journal of Computing, 2016)
The objective of this paper is to present a historical overview of design choices for data acquisition and control systems, from the first developments in CAMAC, through the evolution of their designs operating in VMEbus, Firewire and USB, to the latest developments concerning distributed systems using, in particular, wireless protocols and time-triggered architecture. First part of the overview is focused on connectivity aspects, including buses and interconnects, as well as their standardization. More sophisticated designs and a number of challenges are addressed in the second part, among them: bus performance, bus safety and security, and others.